2016
DOI: 10.3389/fped.2016.00038
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Monitoring during Neonatal Resuscitation for Direct Feedback and Audit

Abstract: Neonatal resuscitation is one of the most frequently performed procedures, and it is often successful if the ventilation applied is adequate. Over the last decade, interest in seeking objectivity in evaluating the infant’s condition at birth or the adequacy and effect of the interventions applied has markedly increased. Clinical parameters such as heart rate, color, and chest excursions are difficult to interpret and can be very subjective and subtle. The use of ECG, pulse oximetry, capnography, and respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 85 publications
0
36
0
1
Order By: Relevance
“…The most recent findings of studies using these models have emphasized how important it is that interventions performed during stabilization or resuscitation are based on scientific data gathered from appropriate animal models [6]. Following from this, noncumbersome and noninvasive physiological measurements in human infants during transition have provided more information and permitted testing of whether observations in animals are similar to those in humans [7]. …”
Section: Introductionmentioning
confidence: 99%
“…The most recent findings of studies using these models have emphasized how important it is that interventions performed during stabilization or resuscitation are based on scientific data gathered from appropriate animal models [6]. Following from this, noncumbersome and noninvasive physiological measurements in human infants during transition have provided more information and permitted testing of whether observations in animals are similar to those in humans [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Research, using physiological monitoring and video recording, has shown that it is often too subjective and suboptimal. In this digital age it is now possible to provide the resuscitation team with a detailed objective display of what is happening to the baby and enable them to optimise their techniques and be confident their treatment is appropriate [42].…”
Section: Discussionmentioning
confidence: 99%
“…Real-time information on vital physiological parameters could improve neonatal resuscitation; with monitoring, these parameters can be kept within the safe range and severe injuries can be prevented 3. Measuring oxygen saturation and heart rate using pulse oximetry is now recommended in the international guidelines.…”
Section: Development Of the Technique Of Recording And Reviewing Neonmentioning
confidence: 99%
“…Although the RFM could remove subjectivity in evaluating neonatal resuscitation,3 it does not provide any interpretation of the signals or a diagnosis. Due to caregivers’ possible inexperience and lack of knowledge, misinterpretation of vital physiological parameters may sometimes occur 24.…”
Section: Development Of the Technique Of Recording And Reviewing Neonmentioning
confidence: 99%
See 1 more Smart Citation